ANALISIS SEMIOTIKA NILAI KARAKTER DISIPLIN DAN JUJUR DALAM FILM ANIMASI TITIPO SEBAGAI MEDIA PEMBELAJARAN SD - Adinda Putri; Sunan Baedowi; Qoriati Mushafanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes discipline and honesty character values in the animated film Titipo season 3 episode 10 "This Is Not Fair Manny" using Charles Sanders Peirce's semiotic triangle approach (sign, object, interpretant). Employing a qualitative descriptive method, primary data from dialogues, visual scenes, questionnaires from 21 fourth-grade students at SD Negeri 1 Gandikan, and interviews with fourth-grade teacher Ibu Levina Ayu Lestari, S.Pd., were analyzed to uncover verbal and nonverbal signs embodying these values. Findings reveal discipline portrayed through Diesel's team responsibility, Manny's perseverance in training to overcome fears, and Diesel's resilience against obstacles; while honesty is depicted via Manny's emotional admission about the rhinoceros, Diesel's frustration outburst, Greeny's clarification, and Manny's apology fostering trust. Titipo proves effective as an elementary school learning medium due to its dynamic visuals captivating digital-native children, enabling repeated imitation of positive values, though teacher supervision is essential. Student questionnaires (average agreement) and teacher interviews affirm Titipo's potential as an innovative character education alternative, aligning with Indonesia's National Education System Law No. 20/2003.